Aprepitant for the Management of Refractory Emesis in a Patient With a Small Bowel Carcinoid Tumor. (1st June 2014) - Kyeremateng, Sam; Boland, Jason W.
ABSTRACT Nausea and vomiting are common distressing symptoms with multiple etiologies. Serotonin and substance P can induce nausea and vomiting by binding to specific receptors (5-hydroxytryptamine3 [5HT3] and neurokinin-1 [NK-1] receptors respectively). Carcinoid tumors, which originate from enterochromaffin cells of the neuroendocrine system, secrete several biologically active amines and peptides, including serotonin and substance P, that are responsible for the distant effects of this tumor. The authors present an 88-year-old lady with metastatic carcinoid tumor, with evidence of carcinoid syndrome. She had nausea and vomiting that became unresponsive to 5HT3 receptor antagonists and other antiemetics. As substance P is released from carcinoid tumors and has a role in the pathogenesis of emesis, the NK-1 receptor antagonist aprepitant was trialed. This provided complete and sustained improvement of the nausea and vomiting until her death 2 months later. This case demonstrates the potential role and rationale of NK-1 receptor antagonists in the management of resistant emesis in patients with carcinoid tumors. Clinical trials are needed to evaluate the efficacy and toxicity of these drugs in the management of emesis in patients with carcinoid syndrome.